2021
DOI: 10.3390/ijms22105351
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Metformin on the Central Nervous System, with a Focus on Epilepsy and Lafora Disease

Abstract: Metformin is a drug in the family of biguanide compounds that is widely used in the treatment of type 2 diabetes (T2D). Interestingly, the therapeutic potential of metformin expands its prescribed use as an anti-diabetic drug. In this sense, it has been described that metformin administration has beneficial effects on different neurological conditions. In this work, we review the beneficial effects of this drug as a neuroprotective agent in different neurological diseases, with a special focus on epileptic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 128 publications
(199 reference statements)
0
25
0
Order By: Relevance
“…However, treatment with AMPK activators could attenuate these behavioral and molecular changes in the pathophysiological profile of metabolic dysfunction (Wang et al 2018 ). Various studies have shown that treatment with metformin is effective in neurological diseases, including high MPTP and increased BDNF (Patil et al 2014 , Lu et al 2016 ), Parkinson’s disease (Choi et al 2010 ; Arbeláez-Quintero and Palacios 2017 ; Lu et al 2020 , Paudel et al 2020 ), epilepsy (H S, Paudel et al 2019 , Demaré et al 2021 ; Sanz et al 2021 , Salvati et al 2022 ), traumatic brain injury (Tao et al 2018 ; Taheri et al 2019 ; Fan et al 2020 ; Rahimi et al 2020 ), neuroprotection of the heart (Zhu et al 2018 , Benjanuwattra et al 2020 , Leech et al 2020 ), and preconditioning in ischemic brain injury (Wang et al 2021a , b , c ). Various studies have shown that BDNF can affect the structure of the anal sphincter (Singh and Rattan 2021 , Singh, Singh et al 2021 ).…”
Section: Metformin and Therapeutic Goalsmentioning
confidence: 99%
“…However, treatment with AMPK activators could attenuate these behavioral and molecular changes in the pathophysiological profile of metabolic dysfunction (Wang et al 2018 ). Various studies have shown that treatment with metformin is effective in neurological diseases, including high MPTP and increased BDNF (Patil et al 2014 , Lu et al 2016 ), Parkinson’s disease (Choi et al 2010 ; Arbeláez-Quintero and Palacios 2017 ; Lu et al 2020 , Paudel et al 2020 ), epilepsy (H S, Paudel et al 2019 , Demaré et al 2021 ; Sanz et al 2021 , Salvati et al 2022 ), traumatic brain injury (Tao et al 2018 ; Taheri et al 2019 ; Fan et al 2020 ; Rahimi et al 2020 ), neuroprotection of the heart (Zhu et al 2018 , Benjanuwattra et al 2020 , Leech et al 2020 ), and preconditioning in ischemic brain injury (Wang et al 2021a , b , c ). Various studies have shown that BDNF can affect the structure of the anal sphincter (Singh and Rattan 2021 , Singh, Singh et al 2021 ).…”
Section: Metformin and Therapeutic Goalsmentioning
confidence: 99%
“…Metformin has been observed to regulate oxidative balance in various studies by inhibiting the complex I enzyme in the electron transport chain (ETC) ( Fontaine, 2018 ; Vial et al, 2019 ; Wang et al, 2019 ). Reactive oxygen species (ROS) production is directly restricted by inhibiting mitochondrial complex I and modulating the respiratory chain ( Sanz et al, 2021 ). Upon metformin administration, ROS production is reduced and an enhanced anti-oxidant system is witnessed ( Ouslimani et al, 2005 ; Diniz et al, 2016 ).…”
Section: Biological Activities Of Metforminmentioning
confidence: 99%
“…Upon metformin administration, ROS production is reduced and an enhanced anti-oxidant system is witnessed ( Ouslimani et al, 2005 ; Diniz et al, 2016 ). In animals, metformin is reported to increase levels of endogenous proteins such as thioredoxin (Trx), sirtuin 3, and glutathione to counteract the attack of free radicals produced during variety of disorders, including age-related neurodegeneration, epilepsy ( Sanz et al, 2021 ), cardiovascular disease, cancer, inflammation, and osteoporosis. The AMPK pathway increases the expression of Trx, an oxidoreductase enzyme.…”
Section: Biological Activities Of Metforminmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes has been linked to an increased risk of epileptic seizures in epidemiologic studies [6][7][8][9] . Some antiglycemic drugs, such as liraglutide, sitagliptin, rosiglitazone, and metformin, have been shown in animal studies to be effective in reducing seizures and improving cognitive impairment [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%